Importance Employee Engagement And Position Promotion On Employee Performance In Small And Medium Business Groups In Banten Province - Hamdan, Hamdan (Publisher Cv. Inara, 2022)
This study aims to determine the influence of Employee Engagement and Position Promotion on Employee Performance in Small and Medium Business Groups in Banten Province. The method used is a descriptive and associative quantitative method. The population of this research is employees with a sample of 81 people. Data was collected using a questionnaire. This study uses regression analysis using SPSS version 23 software Based on the results of hypothesis testing 1 shows employee engagement has a significant effect on employee performance. The results of hypothesis 2 test show that promotion has a significant effect on employee performance. The result of hypothesis test 3 shows that employee engagement and promotion have a positive and significant effect simultaneously on employee performance. The results of this study indicate that there is a significant influence between employee engagement and job promotion variables on employee performance by 3.2 %.